Risk assessment for demoliition works in Malaysia - Nor Rizman, Abas (2010)
This research is aimed at developing an overview as well as assessing the potential hazard involve in demolition operations in Malaysia. It intends to generate perspective insight into the current state of demolition works which in turn, will be beneficially applied to serve as a solid platform for future research and development. This research is divided into three parts. The first part involves the case study of two demolition project that has been carried out which is Lumba Kuda Flats in Johor Babru and Pekeliling Flats in Kuala Lumpur. Both of the case studies have shown -that although risk management was included in the health and safety plan, it only covers the surface of the problem area by only referring to Factories and Machinery Act 1974, Occupational Safety and Health Act 1994 or base on previous project report. The second part of the research is discussion with expert regarding the problems in managing hazards on site. The last part involves the development of the risk assessment system and the implementation of the findings which covers the hazard identification process and risk management for demolition works at UTMKL that suppose to commence on February 2008. However, the project has been postponed to further date that has not, been stated up till now. After taking few factors into consideration, the research has been proceed by making an assumption that the traditional method (deconstruction) will be adopted. Hence, the hazard identification process as well as the control measures involve has been identified. The hazard and control measures involve has been stated in risk assessment form that has been developed. The development of the risk assessment form shows that all the objectives for the research has been achieve. The conclusion that can be drawn is the types of hazard that may be arise on site is depends on the activity during the execution of the demolition project.